NAVIGATING SECOND LANGUAGE ACQUISITION IN A MULTILINGUAL SOCIETY (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article explores the complex process of second language acquisition in multilingual societies. Through a literature review, the paper examines language learning strategies, cultural factors, and the benefits of multilingualism. The findings indicate that multilingual environments positively influence second language acquisition, but effective educational approaches are necessary